Determinant Determinant Factors Of Purchase Decision Among Muslim Consumers In E-commerce: Study in Pati Regency - Redita Apriliana; Darwanto (NUsantara Islamic Economic Journal, 2022)
This study tries to analyze the determinant factors that influence the purchasing decisions of Muslim consumers in Pati who use e-commerce. The object of this research is Muslim consumers in Pati who use e-commerce. There are 100 samples calculated by the Lemeshow formula. The analytical method used is multiple regression with the SPSS 22 analysis tool. The results of this study indicate that Muslim consumer trust in Pati is significant and has an impact on purchasing decisions in e-commerce. Then the ease of use of e-commerce sites or applications is also significant and has an impact on their purchasing decisions in e-commerce. Service quality is significant and influences the purchasing decisions of Muslim consumers in Pati when using e-commerce. Price is an influential and significant determinant of consumer purchasing decisions in e-commerce. Product diversity is significant and has an effect on the purchasing decisions of Muslim consumers in e-commerce.Then the other effect was explained by other factors outside of the factors that were used in this research.